2016
DOI: 10.1021/acs.accounts.5b00534
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Mediated Hydrogen Bonding of Proteinogenic α-Amino Acids on Silicon

Abstract: Understanding the adsorption, film growth mechanisms, and hydrogen bonding interactions of biological molecules on semiconductor surfaces has attracted much recent attention because of their applications in biosensors, biocompatible materials, and biomolecule-based electronic devices. One of the most challenging questions when studying the behavior of biomolecules on a metal or semiconductor surface is "What are the driving forces and film growth mechanisms for biomolecular adsorption on these surfaces?" Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…In the study of cysteine adsorption on Si(111)­7×7, we conclude that the cysteine zwitterionic structure could exist up to 85 °C, while the transitional layer (second adlayer) consisting of interlayer hydrogen bonds are stable even after annealing to 175 °C. , In the present work, no transitional layer is observed and physisorption is found to occur at the second adlayer on the as-formed chemisorbed layer. However, after annealing, the chemical composition of the cysteine film on Si(111)-√3×√3-Ag appears to resemble that of cysteine on Si(111)­7×7, which suggests the presence of a transitional layer on the interfacial layer.…”
Section: Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…In the study of cysteine adsorption on Si(111)­7×7, we conclude that the cysteine zwitterionic structure could exist up to 85 °C, while the transitional layer (second adlayer) consisting of interlayer hydrogen bonds are stable even after annealing to 175 °C. , In the present work, no transitional layer is observed and physisorption is found to occur at the second adlayer on the as-formed chemisorbed layer. However, after annealing, the chemical composition of the cysteine film on Si(111)-√3×√3-Ag appears to resemble that of cysteine on Si(111)­7×7, which suggests the presence of a transitional layer on the interfacial layer.…”
Section: Resultssupporting
confidence: 46%
“…Our proposed mechanism is supported by the presence of both −COOH and −NH 2 features and the corresponding −COO − and −NH 3 + (H-bond related) features in the O 1s and N 1s regions. Formation of H-bonded groups has also been observed in the transitional layer of a cysteine film on Si(111)­7×7 …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In regards to previous simulation studies that considered the presence of multiple amino acids adsorbed on a solid surface, most focused on dimers which were modeled in either the neutral or zwitterionic states. [48][49][50][56][57][58] However, very little has been reported on the modeling of amino acid adlayers on solid surfaces. Notably, a pioneering simulation study by Popa and Paci reported the modeling of methionine adlayers on Au(111).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its common experimental application, relatively complex chemistry in the solid state, yet it's small size which has a major impact on the time of calculations, α glycine has been used as an convenient example in the computational benchmark and new methodologies tests . Some of its application as a model structure include the molecular dynamics, surface adsorption or rotational spectra prediction via calculations. The structure of the α polymorph is also commonly used while performing the GIPAW calculations.…”
Section: Introductionmentioning
confidence: 99%